MANAJEMEN PENGENDALIAN KINERJA PENDIDIK DALAMMENINGKATKAN MUTU PEMBELAJARAN PADA SMPN 59 SURABAYA - Kharisma Ayu Pramesti; Noviana Rahmadhani Putri, Windasari, Agustin Hanivia Cindy (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This article aims to find out about; 1) the process of controlling the performance of educators whether it has been running well and the obstacles faced by educators in improving the quality of learning; 2) knowing whether the quality of learning is in accordance with predetermined standards; 3) knowing whether the performance of educators is able to improve the quality of learning at school well. The subject of this research is educators at SMPN 59 Surabaya which is one of the driving schools. This research uses a qualitative approach and the research method used is descriptive analysis. The data collection techniques used were interviews, observation and documentation at SMPN 59 Surabaya. The results showed that; 1) the control of teachers at SMPN 59 Surabaya has been running well so that the quality of learning also goes well; 2) in controlling the performance of educators to improve the quality of learning at SMPN 59 Surabaya there is a learning community that functions for teachers sharing for smooth learning; 3) The obstacles faced by educators are that there are still some educators who do not fully understand the current technological developments used for the learning process.